2004
DOI: 10.1074/jbc.m404725200
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Inorganic Polyphosphate on the Proteolytic and DNA-binding Activities of Lon in Escherichia coli

Abstract: Lon belongs to a unique group of proteases that bind to DNA and is involved in the regulation of several important cellular functions, including adaptation to nutritional downshift. Previously, we revealed that inorganic polyphosphate (polyP) increases in Escherichia coli in response to amino acid starvation and that it stimulates the degradation of free ribosomal proteins by Lon. In this work, we examined the effects of polyP on the proteolytic and DNA-binding activities of Lon. An order-of-addition experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
72
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(79 citation statements)
references
References 28 publications
5
72
0
1
Order By: Relevance
“…We found that Lon efficiently degrades L24 when Lon and polyP are mixed together prior to the addition of L24, whereas there is little degradation of L24 when it is first mixed with polyP before the addition of Lon. 21) This result indicates that polyP-Lon complex formation is important for the stimulation of protein degradation and that polyP does not act as a tag for Lonmediated degradation. PolyP functions as an adaptor molecule to stimulate a Lon-substrate complex.…”
Section: How Are Ribosomal Proteins Made Available For Degradation?mentioning
confidence: 77%
See 3 more Smart Citations
“…We found that Lon efficiently degrades L24 when Lon and polyP are mixed together prior to the addition of L24, whereas there is little degradation of L24 when it is first mixed with polyP before the addition of Lon. 21) This result indicates that polyP-Lon complex formation is important for the stimulation of protein degradation and that polyP does not act as a tag for Lonmediated degradation. PolyP functions as an adaptor molecule to stimulate a Lon-substrate complex.…”
Section: How Are Ribosomal Proteins Made Available For Degradation?mentioning
confidence: 77%
“…19,20) In contrast to the ribosomal proteins tested, the degradation of a maltose-binding protein (MBP)-SulA fusion was slightly inhibited in the presence of 1.4 mM polyP. 21) Therefore, polyP does not always stimulate Lon-mediated protein degradation.…”
Section: Ribosomal Proteins: Sacrifice Substrates Degraded By the mentioning
confidence: 99%
See 2 more Smart Citations
“…DNA binding by the ATP-dependent Lon (La) protease is evolutionarily conserved from bacteria to man, suggesting that it is an essential property of the protein (1)(2)(3)(4)(5)(6)(7)(8). Purified bacterial Lon has been shown in some experiments to bind doublestranded DNA without apparent sequence specificity when assayed with relatively large DNA molecules (e.g.…”
mentioning
confidence: 99%